David Chipperfield the embedded nomad - Colenbrander, Bernard 1956-; Rapp, Christian 1964- (ArtEZ Press, 2016)
"David Chipperfield was awarded the Netherlands Sikkens Prize for his approach towards the urban context, his talent in re-using existing buildings and monuments, and his subtle and subdued use of colour. Chipperfield was somewhat surprised, because he considered his use of colour and material to be a logical consequence of his views on architecture, not an exceptional achievement. Yet, he interpreted the recognition as encouragement to reflect on the role of colour. Chipperfield's architecture contributes to uniqueness and creates meaningful environments. It is open to change and reinterpretation, because the process of designing, experiencing, and learning never ceases." --Publisher